Kesantunan Bahasa Peserta Diskusi ILC Tema “Tahun Politik Makin Panas: Tampang Boyolali vs Sontoloyo” - Sabrina, Reno Mardhatillah; Satriawan, Nofri (Inovan Publisher, 2025)
This study aims to describe the politeness of the discussion participants in the Indonesia Lawyers Club program theme